Análisis de la narrativa periodística presentada en los noticieros televistazo al amanecer y telediario y su incidencia en los formatos informativos social media institucionales - Mejía Rada, Danny Gabriel (2019)
In recent years, national journalism has evolved through technology and the speed with which these digital media open their doors to web 2.0. Event that has promoted passing from traditional media to digital media at the speed of light, television journalism in Ecuador is a very important source of communication, due to this there are many channels that currently handle other types of platforms as websites where all the information is supported, television broadcast of the news, which place it as a strategic means called cloning. The problem is present in the news media and its adaptation to the new digital platforms as they are obliged to content that is appropriate and reliable sources to avoid misinformation. With this background it is defined that this research has a qualitative-quantitative approach, in such a way, that it is addressed in two points; the one of the qualities and quantities in which it is necessary that they apply interviews and surveys that allow to solve the hypotheses of the problematic one raised on the informative events in the digital means that allow him to modify the current structure to offer better alternatives of communication…..